Notes on a collection of Meconematinae (Orthoptera: Tettigoniidae) from Damingshan, Guangxi, China with the description of a new species - Shi, Fu-Ming; Bai, Jin-Rong; Zhang, Ying; Chang, Yan-Lin (Zootaxa, 2013)
This paper deals with 6 genera and 10 species of the tribe Meconematini from Damingshan, Guangxi, China, one of which is a new species, i.e. Xizicus (Eoxizicus) laminatus Shi sp. nov.